An examination of match official's perceptions of support and abuse in rugby union and cricket in England. Issue 1 (4th May 2019) - Webb, Tom; Rayner, Mike; Thelwell, Richard
ABSTRACT: Sport management literature offers limited research about the reasons for the cessation of match officials. This paper explores match official perceptions of support and abuse in rugby union and cricket in England. Match officials in rugby union and cricket operating at all levels of their sports were surveyed. In total 1228 surveys were completed, presenting a real-life representation of experiences. Results revealed that 49% of rugby union and 45% of cricket match officials experienced abuse at least twice every season, and 51% of rugby union and 47% of cricket match officials believed that abuse had increased, whilst concerns with the training and support provided were identified. Therefore, there is a requirement for the management/support structures assisting match officials to be re-evaluated. As the first empirical paper on abuse and support of match officials in rugby union and cricket, this research advances our understanding about the challenges faced in these sports.